The significance of global design in creation of social life in urban neighbourhoods - Oktay, Derya (My University, 1999)
Today, in many urban residential layouts there is a failure of public use, hence, lack of social interaction. These effects could be explained with the locally oriented design system, which considers only the identity of the neighbourhood and neglects the global structure. Therefore, design should start with thinking of the larger scale for the new development to integrate into and take advantage of the surrounding patterns. Such a design system is called 'global design'. Most essential qualities in implementation of global design are the 'choice of access' to and the 'choice of experience' through the spaces.
Keywords: Choice of access; Choice of experience; Global design; Neighbourhood; Quality of social life